Journalistic Mass Media Management - M. Yoserizal Saragih (Budapest International Research and Critics University, 2020)
This study aims to discuss the Journalistic Mass Media Management. This study use quantitative method. The result shows that Mass media consists of printed mass media and electronic mass media. Print mass media in the form of newspapers, magazines, books, tabloids, and so on. Meanwhile, electronic mass media can be in the form of television, internet and radio. The mass media also has several functions, including an information function, an agenda function, a liaison function for people, an education function, a persuasion function, and an entertaining function. The messages conveyed by the mass media are new, interesting, and important. The effects of the mass media are also very large for society. Self-change in society occurs because of the mass media. The effect of the mass media is also related to the message itself. Today, we know the development of the mass media is very fast. However, it would be nice if the mass media developed to carry messages in accordance with the culture of the Indonesian people. The mass media should provide useful messages for the wider community.